THE ICTY’S CONTRIBUTION TO THE DEVELOPMENT OF PUBLIC INTERNATIONAL LAW (NATIONAL CAPITAL LAW JOURNAL, 2019)
NA
Keywords: International Criminal Tribunal For The Former Yugoslavia; Public International Law; International Humanitarian Law; International Criminal Law; Armed Conflict; Joint Criminal Enterprise; War Crimes; Crimes Against Humanity; Customary International Law; Genocide